1992
DOI: 10.1007/bf01875321
|View full text |Cite
|
Sign up to set email alerts
|

Structure and conformation in solution of the parallel-stranded hybrid α-d(CGCAATTCGC)·β-d(GCGTTAAGCG) by high-resolution 2D NMR

Abstract: The unnatural duplex oligonucleotide alpha-d(CGCAATTCGC).beta-d(GCGTTAAGCG) was analyzed by high-resolution NMR methods. All of the exchangeable imino and nonexchangeable protons of the duplex were assigned. Detection of all 10 of the exchangeable imino protons confirms that a parallel, unsymmetrical duplex is formed. The thermal stability of the parallel duplex is similar to the analogous antiparallel beta-beta duplex. The right handedness of the helix is confirmed by inter-residue [H8/H6-H1'] and [H8/H6-H2"]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Figure 3 presents the FTIR spectra of the two j8dTi2"j8dA"-/3dT" and adT"-|8dA"-/3dT" triple helices (respectively, Figure 3 panels b and c) as well as the spectra of B family form poly(dA)*poly(dT) (Figure 3a) and of an ß duplex ad(CGCAATTCGC).£d(GCGTTAAGCG) (Figure 3d). The latter duplex has been studied by high-resolution 2D NMR (Gmeiner et al, 1992). The NOE data are consistent with a B-form geometry adopted by the a-ß hybrid decamer, with S-type sugar pucker and an anti conformation for the glycosidic bonds.…”
Section: •ßmentioning
confidence: 58%
“…Figure 3 presents the FTIR spectra of the two j8dTi2"j8dA"-/3dT" and adT"-|8dA"-/3dT" triple helices (respectively, Figure 3 panels b and c) as well as the spectra of B family form poly(dA)*poly(dT) (Figure 3a) and of an ß duplex ad(CGCAATTCGC).£d(GCGTTAAGCG) (Figure 3d). The latter duplex has been studied by high-resolution 2D NMR (Gmeiner et al, 1992). The NOE data are consistent with a B-form geometry adopted by the a-ß hybrid decamer, with S-type sugar pucker and an anti conformation for the glycosidic bonds.…”
Section: •ßmentioning
confidence: 58%
“…Featuring a single inversion of stereochemistry at the anomeric carbon (C1‘), α-anomeric ODNs exhibit high nuclease resistance (), stable parallel-stranded duplex formation with complementary DNA and RNA strands ( ), and the ability to impede mRNA translation and viral growth in vitro ( , ). Recently, interest in α-ODNs as antisense tools increased with the development of chimeric α/β-ODNs containing 3‘−3‘ and 5‘−5‘ phosphodiester linkages ( , ), which, unlike purely α-ODNs (), can elicit the RNase H-mediated destruction of complementary RNA strands ( , ).…”
mentioning
confidence: 99%
“…ODNs comprised of α-nucleotides, which differ from their native β-anomeric counterparts by a single inversion of stereochemistry at the C1′ position, exhibit high nuclease resistance (Vichier-Guerre et al 1994) and form stable parallel stranded duplexes with complementary β-DNA and β-RNA (Paoletti et al 1989), yet are incapable of eliciting RNase H activity (Gagnor et al 1989). The NMR structures of a number of short α-DNA/β-DNA duplexes firmly established the formation of a right-handed parallel duplex motif, with Watson-Crick base pairing and S-type sugar puckering throughout (Lancelot et al 1989;Guesnet et al 1990;Gmeiner et al 1992). It has been recently demonstrated that certain ODNs containing both αand β-anomeric segments and local polarity reversals, a design developed in several laboratories (Debart et al 1994;Koga et al 1995) including our own, can promote RNase H cleavage of an RNA target (Boiziau et al 1995;Aramini et al 1998a).…”
Section: [Traduit Par La Rédaction] 410mentioning
confidence: 88%